Transmisi Nilai-Nilai Hidup Berumah Tangga melalui Tradisi Pak Ponjen di Desa Blimbingrejo Nalumsari Jepara - Rohman, Fathur; Yanti, Noor (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
This article aims to identify the meaning of Pak Ponjen tradition in Blimbingrejo Nalumsari Jepara village and the values of married life contained in the tradition. There are two issues raised in this study, including the meaning of Pak Ponjen tradition in Blimbingrejo Nalumsari Jepara village and the values of married life in Pak Ponjen in Blimbingrejo Nalumsari Jepara village. This paper is the result of qualitative research with a case study method conducted in Blimbingrejo Nalumsari Jepara village. The data in this study were collected through observation during the Pak Ponjen ceremony procession, interviews with Pak Ponjen tradition actors, and documentation of writings or documents related to the tradition. The results of this study show that the Pak Ponjen tradition is a form of gratitude from parents to God for completing their duties in raising children to the stage of marriage. That way, the children are ready to live their own lives without parental intervention. This tradition is also a medium for parents to teach their children the values of married life, including: harmony, hard work, caring, frugal living, filial piety, and independence.